RADIOLOGICAL CHARACTERISTICS OF 3D-PRINTED PETG AND TPU AT DIFFERENT INFILL PERCENTAGES FOR BREAST CANCER RADIOTHERAPY BOLUS - Abrar, Luthfia Aqila; Sri Herwiningsih; Johan Andoyo Effendi Noor; Faisal Ahlan Rizaldi; Fatimah Kunti Hentihu (Universitas Mataram, 2026)
Skin-sparing effect causes the radiation dose at a certain depth to be higher than at the skin surface. A tissue-equivalent material namely bolus is required to increase the radiation dose to the skin surface. Conventional bolus is widely used, it poorly conforms to irregular surface, leading to air gaps and compromising dose distribution accuracy. The three-dimensional (3D) printing technology enables the fabrication of 3D-printed boluses to minimize the air gap in conventional bolus applications. In addition, 3D printing is allowed to modify its infill percentage and infill patterns, minimizing both printing time and material usage but resulting in different radiological and dosimetric characteristics. Therefore, it is crucial to evaluate the radiological characteristics of 3D-printed bolus before its application in breast cancer radiotherapy. In this study, the radiological characteristics of 3D-printed Polyethylene Terephthalate Glycol (PETG) and Thermoplastic Polyurethane (TPU) boluses at different infill percentages have been evaluated. This research utilized eight plate-shaped 3D-printed bolus samples with dimensions of 12 cm × 12 cm × 1 cm, at the infill percentages of 20%, 40%, 60%, and 80%. Each bolus sample was scanned using a CT-Simulator to determine its Hounsfield Unit (HU) values and linear attenuation coefficients. The obtained HU values were compared with the HU values of human tissues. The results indicate that both 3D-printed PETG and TPU boluses demonstrate similar equivalency to adipose tissue. Consequently, based on radiological evaluation, PETG and TPU materials are suitable for use in fabricating 3D-printed bolus for breast cancer radiotherapy application.